Standard of proof in adjudicating election petitions : a case for a rights-centric approach in Kenya - Gekombe, Jared (University of Pretoria, 2023)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa)--University of Pretoria, 2023.